Pulmonary Metastatic Choriocarcinoma in a Patient with Ectopic Pregnancy - Fahimeh Nokhostin; Razieh Dehghani Firouz Abadi; Mohammad Bashiri Zadeh (Mashhad University of Medical Sciences, 2017)
Gestational trophoblastic tumor (GTT) most commonly follows a molar pregnancy. In fact, it can occur following gestational events such as induced or spontaneous abortion, ectopic pregnancy, and term pregnancy. In this study, we present the case of a patient with ectopic pregnancy who was treated with a single dose of methotrexate (MTX). The maximum titer of beta subunit of human chorionic gonadotropin (BHCG) was 402. Work up of occult metastatic GTT was carried out following MTX therapy, due to elevated BHCG titer. In the positron emission tomography (PET) scan, a 17-mm lesion was detected in the right lung and treated via thoracotomy resection and adjuvant chemotherapy. Within an 18-month follow up, the patient did not reveal any symptoms and the BHCG titer level did not increase. Findings of this study revealed that after MTX therapy for ectopic pregnancy patients need to be followed up. Moreover, lack of BHCG titer decline, even in low tittering after treatment with MTX, can be related to GTT tumors or inadequate treatment for ectopic pregnancy.